Membangun dan Membina Budaya Organisasi di Lembaga Pendidikan Islam - Maysarah Nur Siti; Hayati Fitri (Al-Qalam Institue, 2022)
Every educational institution has its own culture that characterizes an institution or organization. This culture can distinguish between each culture in an organization with other organizations. In cultural studies, it is stated that organizational culture can determine the performance of a company or an institution, the appearance of the organization and the progress of the organization. And conversely, if the organizational culture is weak it will trigger a decrease in performance and the organization will become unstable. Organizational culture is very important in an institution or agency, in order to be able to shape one's attitudes, values ​​and behavior patterns, so that all members can work well together to achieve common goals, which can be passed on from generation to generation. Islamic organizational culture emphasizes benefit and avoids actions that violate syara' law and the implementation of Maqasid As Syari'ah, namely protecting religion, protecting soul, protecting reason, protecting offspring and protecting wealth and being able to be oriented towards success in this world and the hereafter.